Chikungunya-Induced Arthritis in Reunion Island: A Long-Term Observational Follow-Up Study Showing Frequently Persistent Joint Symptoms, Some Cases of Persistent Chikungunya Immunoglobulin M Positivity, and No Anticyclic Citrullinated Peptide Seroconversion After 13 Years. (19th May 2020) - Guillot, Xavier; Ribera, Anne; Gasque, Philippe
Abstract: Background: Reunion Island was struck by a massive Chikungunya outbreak in 2005–2006. Chikungunya infection is characterized by inflammatory joint symptoms, which may evolve into chronic arthritis. Methods: In this long-term longitudinal observational monocentric study, after the 2005–2006 outbreak in Reunion Island, 159 patients were first referred to a rheumatologist for post-Chikungunya chronic musculoskeletal pain, 73 of them were diagnosed with classifiable Chikungunya-related chronic inflammatory rheumatic diseases (>3 month symptom duration from the initial viral infection). Thirty of these 73 patients were clinically evaluated by a second rheumatologist in 2018–2019. The main objective of this second examination was to estimate the proportion of patients with persistent Chikungunya-related inflammatory joint symptoms after 13 years. Results: Inflammatory joint symptoms persisted in 17/30 patients after 13 years (therefore in at least 23.3% of the 73 patients initially diagnosed with Chikungunya-related inflammatory joint symptoms and 10.7% of the 159 patients referred for post-Chikungunya chronic musculoskeletal pain). In the symptom persistence subgroup, the prevalence of positive autoantibodies (antinuclear or ACPA) was significantly higher – without any seroconversion, Chikungunya IgG and IgM levels were higher, long-term IgM positivity and radiographic damage were more frequent. Overall, after 13 years, pain and fatigue levels remained significant, 5 patients were still treated by methotrexate, 3 by TNF-blockers, highlighting long-term Chikungunya-related patient burden. Conclusions: Such a long-term persistence of Chikungunya-related chronic inflammatory rheumatic diseases had not been reported so far. Furthermore, the long-term Chikungunya IgM positivity we observed in some cases might corroborate the hypothesis of residual viral antigen-driven chronic arthritis.